CONFLICT OF INTEREST - Jabbar S. Hassan (The Iraqi Journal of Medical Sciences, 2022)
Conflict of interest (COI) in peer review journals is a serious issue that earn more attention than it currently receives. COI can influence reviewers' or editors' decisions in favor of or against a project. There is no universal description of COI in the medical and scientific world; it is generally defined as a set of situations, in which a major professional interest is overly influenced by a secondary one(s) authors, editors, and reviewers may all be subject to COI. The majority of COI discussion in scientific papers has centered on the impact that authors' financial and nonfinancial (i.e., personal or professional) circumstances have the impact that personal (or professional) interests can have on research integrity. Keywords: Conflict of interest, authors, editors, reviewers, budget Citation: Hassan JS. Conflict of interest. Iraqi JMS. 2022; 20(1): 1-2. doi: 10.22578/IJMS.20.1.1